Belle Dalam Dua Dunia: Animasi Beauty And The Beast Tahun 1991 dan Film La Belle Et La Bête Tahun 2014 - Jinanto, Damar (Urban: Jurnal Seni Urban, 2017)
The ideology of a text can be seen in a story, and one can see the message behind a story, even though the story is a popular one that can be reused in many versions. Theories within the framework of media adaptation can be used to interpret changing ideologies behind a text that transformed alongside developing issues, even if the story is only told in a different medium. This is visible on the French popular folktale, La Belle et La Bête (Beauty and the Beast), that was adapted into animation film by Walt Disney Pictures (1991), and the live action French film by Christophe Gans (2014). The battle of ideologies can be seen through the reconstruction of Belle’s story by Walt Disney Pictures, through Belle’s leitmotif, and Christophe Gans’s deconstruction that he did by removing, changing, or adding narrative and cinematographic materials that were present in the Disney version. Ideologi teks dapat tampak di sebuah karya agar mampu ditemukan pesan yang ingin disampaikan walaupun ceritanya merupakan sebuah cerita populer yang dapat dibuat berulang kali dalam berbagai versi. Kajian alih wahana untuk membaca ideologi teks yang berbeda dapat dikaitkan dengan isu yang sedang berkembang di zamannya, walaupun dengan cerita yang diangkat dari sumber yang sama. Hal ini terjadi pada dongeng populer Prancis, La Belle et La Bête (Beauty and the Beast) yang dialihwahanakan menjadi animasi oleh Walt Disney Pictures tahun 1991 dan film Prancis versi live action karya Christophe Gans tahun 2014. Pertarungan ideologi terlihat dari rekonstruksi kisah Belle oleh Walt Disney Pictures melalui leitmotif karakter Belle dan dekonstruksi yang dilakukan Christophe Gans dengan menghilangkan, mengubah, atau menambahkan materi naratif dan sinematografis yang sudah dibangun di versi animasi Disney.